Academic texts: Social science - Språkbanken Text (University of Gothenburg, 2024)
A corpus with academic texts

En korpus med akademiska texter
Akademiska texter: Samhällsvetenskap
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik